1995
DOI: 10.1074/jbc.270.25.15059
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Factor-4 Inhibits the Mitogenic Activity of VEGF121 and VEGF165 Using Several Concurrent Mechanisms

Abstract: The 121-amino acid form of vascular endothelial growth factor (VEGF121) and the 165-amino acid form (VEGF165) are mitogenic for vascular endothelial cells and induce angiogenesis in vivo. VEGF165 possesses a heparin binding ability and in the absence of heparin-like molecules does not bind efficiently to the VEGF receptors of vascular endothelial cells. The binding of 125I-VEGF165 to the VEGF receptors of endothelial cells, and the heparin-dependent binding of 125I-VEGF165 to a soluble extracellular domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 50 publications
6
130
1
1
Order By: Relevance
“…Further, it has been shown that different CXCL4/PF-4 peptides compete with FGF-2 or VEGF by inhibiting their binding to FGF or VEGF receptors, respectively, or reduce heparin-induced FGF-2 dimerization, resulting in the angiostatic activity (21,31,44,45). However, other mechanisms seem to be involved as well because an analogue of CXCL4/PF-4 that lacks affinity for heparin still retains its angiostatic activity (46), and CXCL4/PF-4 also inhibits the function of VEGF-121, an isoform with deficient heparin-binding ability (47). Recently, an interaction of CXCL4/PF-4 with integrins has been described that might be implicated in angiogenesis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been shown that different CXCL4/PF-4 peptides compete with FGF-2 or VEGF by inhibiting their binding to FGF or VEGF receptors, respectively, or reduce heparin-induced FGF-2 dimerization, resulting in the angiostatic activity (21,31,44,45). However, other mechanisms seem to be involved as well because an analogue of CXCL4/PF-4 that lacks affinity for heparin still retains its angiostatic activity (46), and CXCL4/PF-4 also inhibits the function of VEGF-121, an isoform with deficient heparin-binding ability (47). Recently, an interaction of CXCL4/PF-4 with integrins has been described that might be implicated in angiogenesis (48).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that some secreted proteins, including soluble VEGF receptor 1, platelet factor 4, thrombospondin, ADAMTS1 and CTGF, bind to VEGF and inhibit angiogenic activity (Kendall and Thomas, 1993;Gengrinovitch et al, 1995;Gupta et al, 1999;Luque et al, 2003;Inoki et al, 2002;Jang et al, 2004). As one of these proteins, CTGF is typically expressed in fibroblasts (Brigstock, 1999), we considered the possibility that CTGF might function as an inhibitor of VEGF from fibroblasts.…”
Section: Angiogenic Activity Of Vegf From Fibroblasts In a Nontumor Ementioning
confidence: 99%
“…However, the mechanism by which vascular quiescence is maintained in normal tissues, wherein VEGF is widely expressed (Berse et al, 1992;Hanahan and Folkman, 1996), remains unclear. Several secreted proteins have been reported to bind and sequester VEGF (Kendall and Thomas, 1993;Gengrinovitch et al, 1995;Gupta et al, 1999;Inoki et al, 2002;Luque et al, 2003). This type of regulation could account for the vascular quiescence in the presence of VEGF, although in most tissues except the cornea (Ambati et al, 2006), the relevance of these proteins to vascular control has yet to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Although being structurally a chemokine, PF-4 lacks chemotactic activity on neutrophils and T cells (15,16). Apart from inducing short term responses on PMN, PF-4 is involved in long term differentiation and regulatory processes such as the control of EC and fibroblast proliferation (17)(18)(19) and the support of the survival of hemopoietic stem cells and progenitor cells (20). Moreover, PF-4 suppresses IL-2 mRNA transcription and the release of IL-2 in activated human T cells, corresponding to its inhibitory effect on T cell proliferation and release of IFN-␥ (15).…”
mentioning
confidence: 99%